Reimagining Sustainable Organization Perspectives on Arts, Design, Leadership, Knowledge and Project Management - Jevnaker, Birgit Helene (Springer Nature, 2022)
This open access book reimagines a deeper sustainability in dynamic organization. Offering multiple perspectives on arts, design thinking, leadership, knowledge and project management, Reimagining Sustainable Organization addresses our need for thinking and coping differently when facing the many unknowns of real-life enterprises in society. Drawing on process philosophy, real-world case studies, and examinations of business practices as well as management research, the authors explore knowledge creation towards reimagining sustainable organization. The book includes frameworks and conceptual tools as well as insights for further explorations. This book will be of interests to students, scholars and teachers, and practitioners who are studying sustainable organization, greener management, leadership ideas, or knowledge and project management. It covers future pressing issues also for the professionals involved in co-creative work across organizational boundaries. This is an open access book.